Talking to Dragons : The Enchanted Forest Chronicles, Book Four - Patricia C. Wrede (Belmont, CA, United States Cengage Learning, Inc, 2003)
One day, Daystar's mom, Cimorene, hands him a magic sword and kicks him out of the house. Daystar doesn't know what he is supposed to do with the magic sword, but knowing Cimorene, he's sure it must involve a dragon or two!
Keywords: Science Fiction -- Science Fiction; Fantasy -- Fantasy